2009
DOI: 10.1017/s0266462309090539
|View full text |Cite
|
Sign up to set email alerts
|

Health technology assessment in Italy

Abstract: Objectives:The aim of this study was to review the history of health technology assessment (HTA) in Italy. Methods: Founded in 1978, the Italian National Health Service (NHS) has been strongly regionalized mainly after a constitutional reform, which started a devolution process. HTA started in the 1980s at the National Institute of Health and in a few University Hospitals, with a focus on big ticket technology: that process was driven by clinical engineers. Results: In recent years, HTA is becoming an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 6 publications
0
24
0
6
Order By: Relevance
“…Por esta razão, se a decisão deve ser tomada em um nível organizacional, evidências e dados devem ser também coletados e analisados no contexto organizacional (6), (7).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por esta razão, se a decisão deve ser tomada em um nível organizacional, evidências e dados devem ser também coletados e analisados no contexto organizacional (6), (7).…”
Section: Discussionunclassified
“…Políticos, gestores hospitalares, médicos e outros profissionais estão cada vez mais inseridos na responsabilidade em adotar os conceitos de ATS nos seus serviços (6) , (7).…”
Section: Discussionunclassified
“…In Italy, hospital-based HTA activities are reported in several hospitals, and hospital-based HTA is considered the real driver of the country's HTA movement [3]. One example is the HTA unit at the Policlinico A. Gemelli in Rome, a university health centre comprising five healthcare organizations covering acute, rehabilitation and nursing home care [4,18].…”
Section: The Hta Unitmentioning
confidence: 99%
“…For instance, in Canada, the Canadian Agency for Drugs and Technologies in Health (CADTH) is the entity in charge of HTA at the national level, whereas some Canadian provinces, such as Quebec and Ontario, have their own HTA agencies at the provincial level [2]. In Italy, the National Agency for Regional Healthcare Services (AGENAS) conducts some HTA activities at the national level, and several of the 21 regions of the country also perform HTA activities at the regional level [3].…”
Section: Introductionmentioning
confidence: 99%
“…Within EU context, limited number of studies analysed the role of HTA in decentralised systems and showed that increasing autonomy assigned to the lower levels of government usually fosters the development of HTA programmes and activities at the regional level leaving the role of national level HTA bodies rather ambiguous [11][12][13][14][15][16]. In all the studies, regional models usually appear to be very different among them in terms of organization, institutional framework, stakeholders and aims.…”
Section: Introductionmentioning
confidence: 99%